(untitled) (Journal of Academic Research, 2024)
Machine Translation (henceforth MT) is the use of a computer to convert a text from one language to another. In recent years, machine translation started to emerge as a tool in second language teaching and learning classes in order to facilitate the process of learning English as a second/foreign language. Teaching writing has been considered as one of the challenges that English Foreign Language (henceforth EFL) teachers and students face in EFL classes. Recently, EFL students around the world started to employ machine translation in their writing process. Therefore, this paper aims to investigate Libyan EFL students’ attitudes towards the use of machine translation in EFL writing. In addition, this paper aims to highlight the obstacles that face Libyan students when using machine translation in EFL writing. The sample of the study consists of 32 Libyan EFL university students from the Department of English and the Department of Translation, Faculty of Languages and Translation, Misurata University, Misurata, Libya. In order to achieve this aim.